Effect of Anoxia on Energy Charge and Protein Synthesis in Rice Embryo - Mocquot, Bernard (1981)
Energy charge, adenine nucleotide levels, and protein synthesis were studied during the transfer of rice seedlings from air to anoxia. Within minutes, the energy charge value dropped from 0.90 in air to 0.50 in the seed and 0.60 in the coleoptile after the transfer to a nitrogen atmosphere, and then increased to a value of 0.80 during the subsequent hours. The sum of nucleotides also dropped to 60% of the value in air in the seeds and to 30% in the coleoptiles. However, during the anaerobic growth of coleoptiles, a considerable increase in the nucleotide pool occurred. The incorporation of amino acids into proteins was measured at different stages in anoxic treatment. In rice embryo, we observed a considerable protein synthesis correlated with a high value of energy charge under anoxia. The analysis of labeled proteins by two-dimensional polyacrylamide gel electrophoresis showed a modified pattern of polypeptides synthesized during anoxic treatment. Some of these proteins were intensively labeled and appeared to be induced by anaerobic treatment. Our data indicate that high metabolic activity occurs in rice embryo under anoxia, which can be correlated with a high energy charge value. These phenomena may be part of the mechanisms which permit the adaptation of rice embryos to anaerobiosis.